Penerapan Model Pembelajaran Teaching Factory (TEFA) pada Materi Konsep Dasar Kelistrikan Sepeda Motor Terhadap Hasil Belajar Siswa Kelas XI TBSM SMK Negeri 1 Nisam - Zainal Abidin; Siraj Siraj; Islami Fatwa; Abu Bakar; Muliana Muliana (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
This research aims to find out: (1) Improvement in student learning outcomes, (2) Student responses, (3) Find out whether there is an increase in student and teacher activity, after implementing the taching factory learning model on basic electrical concepts material in class XI TBSM SMK Negeri 1 Nisam. The type of research used is Quasi Experimental Design using a non-equivalent control design. The sampling technique used was 40 students consisting of 20 class XI TBSM 2 students as the experimental class and 20 TBSM 1 students as the control class. Data collection instruments use multiple choice questions and questionnaires. The research results show that: (1) There is an increase in student learning outcomes after implementing the teaching factory learning model on basic motorbike electrical concept material with an average n-gain score for the experimental class of 0.70, which is in the medium category, in the control class the average is n -gain score of 0.16 is in the low category. (2) Student response questionnaire after applying the teaching factory learning model to the basic concepts of motorbike electricity in class XI TBSM SMK Negeri 1 Nisam is in the very good category with an average score of 83%. (3) teacher activities are in the good category with an overall average score of 3.42 with a percentage of 85.5%, while student activities are in the good category with an overall average score of 3.33 with a percentage score of 83%.